Defining the mechanisms of inflammation that underlie the pathogenesis of ovine footrot - Maboni, Grazieli (2017)
Ovine footrot is a bacterial infection of the ovine interdigital skin with a significant welfare and economical concern for the sheep industry globally. Footrot is a major cause of lameness in sheep and it is characterised by two different clinical presentations, interdigital dermatitis (ID) and under-running footrot. The aetiology of this disease is complex with Dichelobacter nodosus as the essential pathogen initiating under-running footrot lesions, however the role of other bacteria, including Fusobacterium necrophorum and Treponema spp., and the roles of other bacterial populations in healthy, ID and footrot feet remain unclear. The severity of footrot is thought to be exacerbated by the intense inflammatory response against the infection; nevertheless, there is little information in the literature regarding the ovine immune response to this disease. In this context, the hypothesis of this study is that the pathology of footrot is a host mediated expression of local immune responses, in association with bacterial colonisation, leading to severe inflammation that can progress to under-running lesions. This hypothesis was investigated through the determination of bacterial prevalence and load using qPCR and host gene expression studies using RT-qPCR and RNA sequencing. Moreover, a 3D skin explant model was developed for in vitro infection studies. Key findings include that the highest prevalence and load of D. nodosus was on feet with ID and the vast majority of samples from UK sheep contained virulent D. nodosus strains; notably, the more pathogenic subspecies of F. necrophorum was found in these samples. In addition, a comparison of bacterial colonisation on the ovine interdigital skin surface and within the skin demonstrated that bacterial prevalence and load differed between those two locations. Gene expression analysis revealed that inflammation, as marked by mRNA expression levels of CXCL8 and IL1β, central mediators of immune response in the skin, were associated with virulent D. nodosus in footrot affected feet. This suggests that D. nodosus colonisation may impact on the inflammatory mechanisms involved in footrot. The global gene expression study (RNA sequencing) showed 34 significantly expressed genes in footrot samples indicating upregulation of the local inflammatory and innate immune responses, whilst little association of the local adaptive immune response. A 3D skin model culture was developed and infection with D. nodosus strains for 28h was demonstrated by qPCR and FISH and resulted in the release of IL1β and CXCL8 in the culture media. Hence, this confirms a role for IL1β and CXCL8 in the early local response to D. nodosus infection. Taken together, the data presented in this thesis may potentially endorse our hypothesis that the separation of the hoof horn from the sensitive underlying tissue is led by the host expression of local immune responses in association with bacterial colonisation.